American Productivity Center (APC) and Craig-Harris Productivity Model method in measuring the productivity of customs companies - Ricky Ardianto; Ribangun Bamban Jakaria (Procedia of Engineering and Life Science, 2021)
The purpose of this study is centered on measuring the total and partial productivity of customs companies using the American Productivity Center (Apc) Method and the Craig-Harris Productivity Method where the difference between the two is the Craig-Harris Productivity Method directly measures the level of total efficiency obtained from company growth. overall while the American Productivity Center (Apc) method is a measurement to determine the level of the productivity index, profitability and price improvements. The results obtained from measurements in 2018 to 2019 for twenty-four periods are the productivity index of the APC model, the largest decrease in index occurred in capital input in April 2019, which decreased by 22.06%, while with the Craig-Harris Method the largest decrease in productivity figures occurred in power input. Employment in June 2019 decreased by 25.077% from the initial period. From the results of the two methods, there are differences in measurement results, namely the largest decrease in APC occurs in the Capital variable, while the largest decrease in the Craig-Harris Method occurs in Labor and the smallest decrease in productivity occurs in Material input.